Teach yourself visually Excel 2010 - McFedries, Paul (Teach yourself visually, 2010)
Clear, step-by-step screen shots show you how to tackle more than 150 Excel 2010 tasks. Each task-based spread covers a single technique, sure to help you get up and running on Excel 2010 in no time